Análise de relatório público de monitoramento de qualidade de recursos hídricos - Ribeiro Júnior, Oséias (Universidade Federal de São Carlos, 2021)
The importance of water for life and for the economy, its heterogeneous availability, and the different interests involved in its uses brought the need for Water Resources Management. This management uses water monitoring data as a reference for decision making. Monitoring networks can establish benchmarks and identify trends in water quality, which is needed for river basin planning. The objective of this study was to analyze the monitoring reports of the Nacional Water Agency (ANA) and Environmental Company of the São Paulo State (CETESB) to suggest improvements that can strengthen the monitoring networks so that they can be used in more complex applications in water planning. Additionally, it aims to propose the use of monitoring data for modeling of water bodies in environmental licensing. For data analysis, it was used information from the UGRHI-06 region (Alto Tiete), CETESB, InfoÁGUAS database, meta data from the ANA repository, and Electric Energy and Water Department (DAEE) for the same region were used. As a quality reference, the nine parameters that make up the Water Quality Index (IQA) were used to check the possibility of using public reporting data in situations that the system modeling may be required. The water quality data series showed some temporal gaps that make it impossible to set up a robust database and compare it with hydrological data, demonstrating that the current monitoring system has its importance, but it is not mature for more complex applications.
Analyses of public monitoring reports of water resources quality
Keywords: Monitoramento de água; Gestão de recursos hídricos; Qualidade das águas.; Water monitoring; Water resources management; Water quality; Water management; ENGENHARIAS